Theoretical and Conceptual Reflection Regarding Corporate Criminal Responsibilities Influencing the Formulation of Laws - Fitriani Rahmadia (University of Jember, 2020)
In Indonesia, the development of the corporation as the subject to criminal acts takes place outside the Criminal Code, regulated in special legislation. While the Criminal Code itself still adheres to the subject of criminal acts in the form of people, the corporation (juridical person) appears as a subject that can commit a crime and should also be accountable in criminal law. However, this condition has not been realized concretely in our Criminal Code. The formulation policy regarding corporate criminal liability for victims of corporate crime that exists or is currently in force has not been able to realize the corporate criminal liability. Although there are sanctions that can be imposed on corporations, most of these provisions only protect potential victims and are not responsible for actual or real victims. In other words, the current formulation policy has not been able to ensnare and impose criminal sanctions on corporations who commit crimes, especially criminal sanctions which are oriented to the fulfillment or restoration of victims' rights in the form of compensation payments after the crime. This paper will discuss the position and the responsibility of the corporation as a subject of criminal law in Indonesia and analyze policy formulation of the Criminal Code and the draft of the Criminal Code that related to corporate responsibility as a legal subject. Keywords: Corporate Criminal Responsibilities, Criminal Law, Corporate Responsibility.